COMPARATIVE EVALUATION OF THE PRODUCTIVITY OF WINTER CROP VARIETIES WHEN GROWN IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Voloshchuk, Alexandra Petrovna; Voloshchuk, Ihor Stepanovych; Konyk, Hryhoriy Stanislavovich; Dzyubailo, Andriy Hrihorovich; Hlyva, Valentyna Viktorivna; Vorobyova, Yulia Victorivna; Nereshko, Halyna Stepanivna; Sluchak, Oksana Maksymivna (Journal of Agricultural Sciences (Belgrade), 2023)
The aim of the study was to determine the parameters of adaptability and productivity of winter crops: common wheat, sowing rye, and triticale varieties of different originating institutions for cultivation in the Western Forest-Steppe zone over a three-year period (2019–2021) according to general scientific methods: working hypothesis - to select areas of scientific research, experience, observation, analysis; special: field, laboratory, method of morphological analysis; mathematical and statistical - correlation, variation, dispersion. The object of the research were varieties of winter crops, listed in the "State Register of Plant Varieties Suitable for Distribution in Ukraine" in 2014–2015, in particular: soft wheat: Vodogray bilotserkivsky, Oberig Myronivsky, Mudrist odeska; sowing rye: Knyazhe, Kobza, Kharkivyanka; triticale: Markian, Molfar, Obrij myronivsky. The results showed that with the basic growing technology and favorable weather conditions, the varieties of winter crops at the time of the cessation of the autumn vegetation had optimal development, accumulated a sufficient amount of sugars in the tillering nodes (26.9–27.1%), which contributed to a high percentage of overwintering (96.6 - soft wheat, 94.9 - sowing rye, 94.2 - triticale). The largest leaf surface area in the third macrostage ВВСН 37–39 was formed by the following varieties: soft wheat (winter) - Oberig Mironovsky (61.5 thousand m2 ha-1), sowing rye (winter) - Knyazhe (64.8 thousand m2 ha-1), triticale (winter) - Molfar (70.2 thousand m2 ha-1). The degree of damage to the ear by Septoria and Fusarium pathogens depended on the presence of resistance genes of various varieties and crops, the infectious load of the composition of the fungus populations in the infection zone, and environmental factors. In soft wheat, the average indicators for varieties were 3.3% with septoria and 2.4% with fusariosis of the ear; sowing rye, respectively, 2.4 and 1.9%, triticale - 1.9 and 1.8%. Grain productivity of soft wheat varieties varied from 4.88 (Mudrist odeska) to 5.39 t ha-1 (Oberig Mironovsky); rye - from 5.55 (Kharkivyanka) to 6.32 t ha-1 (Kobza); triticale - from 6.45 (Markiyan) to 6.74 t ha-1 (Obrij myronivsky). When overstaying grain "on the vine" for 12 days from full ripeness of the grain, the average weight loss of 1000 grains in soft wheat (winter) was 6.0%, rye (winter) - 10.5, triticale (winter) - 6.6 %. The results obtained allow us to conclude that optimal parameters of adaptability and productivity of the studied winter grain crops can be included in the variety replacement of the most environmentally plastic varieties. This will contribute to the production of a sufficient amount of basic seeds to ensure the area under crops in the region and the efficiency of seed production.
Keywords: Key words: soft wheat (winter), sowing rye (winter), triticale (winter), disease, yield, weight of 1000 grains.